Maternal perception of sickness as a risk factor of stunting in children aged 2-5 years - Dellu, Maria Fatima Dete; Mexitalia, Maria; Rosidi, Ali (Universa Medicina, 2016)
BackgroundStunting in children is caused by past nutritional problems, adversely affects the physical and mental characteristics of children and is a well-established child-health indicator of chronic malnutrition. Socio-cultural factors can affect parenting, thereby indirectly affecting child growth. The objective of this study was to determine socio-cultural factors and parental short stature as risk factors of stunting in children aged 2 to 5 years.MethodsThe study used a quantitative approach with case control design and a qualitative approach with in-depth interview. The study subjects were children aged 2-5 years, consisting of 45 cases of stunting and 45 controls (normal subjects). Socio-cultural data were obtained through interviews with the mothers, while height was measured with a stadiometer. Data were analyzed using chi square and logistic regression tests to calculate the odds ratio (OR).ResultsThe logistic regression test showed that maternal perception of sickness as a curse (OR=7.43; 95% CI: 2.37-23.21), stopping breastfeeding at <24 months (OR=6.01;95% CI: 1.83-19.69) and low household expenditure for food (OR=5.78;95% CI: 1.28-26.01) were risk factors of stunting incidence with a probability of 73.8%. The most dominant risk factor of stunting was maternal perception of sickness (OR=7.43 95% CI: 2.37-23.21). ConclusionMaternal perception of sickness was the most dominant risk factor of stunting in children 2-5 years of age. A multidisciplinary approach is needed to address the range of raised issues and so combat stunting in children.